ADI-FDTD Method for Two-Dimensional Transient Electromagnetic Problems (Communications in Computational Physics, 2018)
An efficient and accurate numerical scheme is proposed for solving the transverseelectric (TE) mode electromagnetic (EM) propagation problem in two-dimensionalearth. The scheme is based on the alternating direction finite-difference time-domain(ADI-FDTD) method. Unlike the conventional upward continuation approach for theearth-air interface, an integral formulation for the interface boundary is developed andit is effectively incorporated to the ADI solver. Stability and convergence analysis togetherwith an error estimate are presented. Numerical simulations are carried outto validate the proposed method, and the advantage of the present method over thepopular Du-Fort-Frankel scheme is clearly demonstrated. Examples of the electromagneticfield propagation in the ground with anomaly further verify the effectiveness ofthe proposed scheme.